Use of sequential quadrupling dose regimens to study efficacy of inhaled corticosteroids in asthma. Issue 1 (23rd December 2003) - Phillips, K; Oborne, J; Harrison, T W; Tattersfield, A E
Abstract : Background: Inhaled corticosteroids are widely used to treat asthma. There is a need to be able to compare different inhaled corticosteroids and different doses of an inhaled corticosteroid to determine potency and dose equivalence, but measuring efficacy in a dose related manner is difficult because of their slow onset of action. There is uncertainty about the role of sequential dosing regimens and the best end point for such studies. We have explored the use of sequential quadrupling dose regimens and a range of end points to assess the response to budesonide in subjects with asthma. Methods: 21 subjects with mild asthma, aged 18–65, took part in a randomised three way crossover study comparing two sequential and one non-sequential regimen, separated by at least 3 weeks. The sequential regimens consisted of increasing doses of inhaled budesonide (100, 400 1600 μg/day) with each dose being given for 1 or 2 weeks; the non-sequential regimen consisted of 1600 μg/day for 2 weeks with end points measured after 1 and 2 weeks. The end points studied included the provocative dose of adenosine monophosphate causing a 20% fall in forced expiratory volume in 1 second (PD20 AMP), lung function, symptoms, and bronchodilator use. Results: There was a dose related increase in PD20 AMP with both sequential dose regimens. The increase in PD20 AMP ranged from 1.49 doubling doses (DD) following the lowest dose (100 μg/day) to 3.1 DD following the highest dose (1600 μg/day) in the 1 week sequential regimen and from 1.98 to 4.03 DD in the 2 week sequential regimen; standard deviations (SD) for the changes in PD20 AMP ranged from 1.3 to 2.6 DD. Changes in forced expiratory volume in 1 second (FEV1 ) and morning peak expiratory flow rate (PEFR) were dose related but small and more variable (maximum change in FEV1  = 148 ml, SD 228 ml), while changes in evening PEFR, symptoms, and bronchodilator use were small and not dose related. Change in PD20 AMP after budesonide 1600 μg did not differ significantly between regimens. Conclusion: Combining PD20 AMP measurements with a sequential regimen of three quadrupling doses of an inhaled corticosteroid given for 1 or 2 weeks provides clear dose-response curves for comparative studies. PD20 AMP is a more sensitive end point for this purpose than FEV1, PEFR, symptoms, or relief inhaler use.